Training Kit Kendali Motor Induksi berbasis Inverter Tiga Fasa: Analisis Uji Kelayakan - Doni Tri Putra Yanto; Hastuti Hastuti; Andrian Andrian; Putri Ani; Nizwardi Jalinus; Ridwan Ridwan (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This study discusses the analysis of the feasibility test of the three-phase inverter-based Induction Motor Control Training Kit (TKKMI) which is carried out before it can be used and applied in the laboratory as a medium or practicum equipment in the learning process of the Electric Motor Control Practicum. This feasibility test analysis is carried out to ensure that the device meets the criteria as practicum equipment or practicum learning media and can function properly according to its function. Feasibility test analysis is a testing activity in a laboratory that includes testing the safety aspects. aspects of electrical parameters, as well as device performance. The results showed that the TKKMI device based on a three-phase inverter met the criteria and standards as a media or practicum equipment in the learning process of electric motor control practicum for D3 electrical engineering vocational education students. Thus, it can be concluded that the TKKMI device is feasible to be used as practicum equipment in the laboratory for the learning process of the 3-phase induction motor control practicum.